Gas chromatography-mass spectrometry (GC/MS) reveals urine metabolites associated to light and heavy infections by Schistosoma mansoni in mice - Loyo, Rodrigo Moraes (2021)
Oswaldo Cruz Foundation. Aggeu Magalhães Institute. Laboratory and reference service on Schistosomiasis. Recife, PE, Brazil / University of Auckland. School of Biological Sciences. Auckland, New Zealand.